CLINICAL EVALUATION OF ERAND MOOLADI BASTI IN THE MANAGEMENT OF GRIDHRASI W.S.R. TO SCIATICA - A CASE STUDY - Sharma, Pooja; Divya, Kajaria (International Journal of Ayurveda and Pharma Research, 2019)
Background: Large numbers of population suffer from the low back-pain. Prevalence increases linearly from third decade of life on, until the 60 years of age, being more prevalent in woman. Sciatica most commonly occurs when a herniated disk, bone spur on the spine or narrowing of the spine (spinal stenosis) compresses part of the nerve. It is commonly occurs due to the compression of lumbar nerves L4 or L5 or sacral nerves S1, S2 or S3 or by the compression of the sciatic nerve itself. This causes inflammation, pain and often some numbness in the affected leg. Gridhrasi is the one amongst the 80 types of Nanatmaja disorders of Vatavyadhi, It starts from Kati- prishta (pelvic region and Lumbosacral) radiating to Jangha (thigh) and Pada (feet) with impairment of lifting the leg. The gait of the person is very similar to vulture (Gridhra) hence the name is given as Gridharsi. Material and Method: A case controlled clinical study on a known case of Gridharsi has been done in All India Institute of Ayurveda Hospital. The treatment was planned on the basis of principles of Ayurveda mentioned in the context of Gridharsi including Erand-mooladi basti and oral medications. Result: after the whole course of treatment, patient got 70% relief in all sign and symptoms and changes in gait limping gait to normal gait. Conclusion: It can be concluded that Erand-mooladi basti and oral medications is more effective in Gridhrasi management.